Super-tensile, compression-resistant and double-physical-crosslinking conductive hydrogel based on phytic acid as well as preparation method and application of super-tensile, compression-resistant and double-physical-crosslinking conductive hydrogel

By introducing hexadecyl methacrylate and cetyl trimethylammonium bromide into the conductive hydrogel, a dual physical crosslinking network is formed, which solves the low rebound efficiency, poor mechanical properties and sensitivity of conductive hydrogel materials. The problem of low achieves high mechanical performance and high sensitivity, and is suitable for health monitoring and human-computer interaction and other fields.

CN119490624AActive Publication Date: 2025-02-21NORTH CHINA ELECTRIC POWER UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411634332.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing conductive hydrogel materials have low rebound efficiency, poor mechanical properties and low sensitivity, which limit their applications in health monitoring, human-machine interaction and wearable devices.

Method used

By introducing hexadecyl methacrylate as a hydrophobic unit, combining hexadecyl trimethylammonium bromide and acrylamide polymer chains, a dual-physical crosslinking network is formed to achieve high rebound performance and high sensitivity.

Benefits of technology

It achieves high mechanical properties of the hydrogel (strength is 378.25kPa, elongation of break is 859.5%) and high sensitivity, suitable for health monitoring, human-computer interaction and wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490624A_ABST
    Figure CN119490624A_ABST
Patent Text Reader

Abstract

The invention discloses super-tensile, compression-resistant and double-physical-crosslinking conductive hydrogel based on phytic acid as well as a preparation method and application of the super-tensile, compression-resistant and double-physical-crosslinking conductive hydrogel. The main preparation process comprises the following steps: adding hexadecyl methacrylate into a mixed solution of a surfactant hexadecyl trimethyl ammonium bromide and lithium chloride, completely dissolving, adding an acrylamide monomer, phytic acid and an initiator to obtain a mixed solution, and obtaining the hydrogel by adopting a micelle copolymerization method. The hydrophobic association hydrogel has the advantages that a network structure contains physical interactions such as hydrogen bonds, electrostatic interaction and hydrophobic association, so that the hydrophobic association hydrogel has relatively high mechanical strength and rebound resilience. The hydrophobic association hydrogel sensor is simple in preparation method, rich in raw materials and low in price, has the properties of high mechanical strength, high sensitivity, high rebound resilience and the like compared with traditional hydrogel, and has potential application value in the fields of tissue engineering, flexible electronic skin, intelligent sensors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive hydrogel materials, and in particular relates to a super-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid, and a preparation method and application thereof. Background Art

[0002] Hydrogel is a three-dimensional cross-linked network composed of hydrophilic polymer molecular chains dispersed in water through multiple cross-linking effects. Since hydrogel contains a large amount of water, this soft and wet property gives hydrogel many excellent properties, so it has broad application prospects in many fields such as flexible sensing, electronic skin, wound dressing, health monitoring, etc. However, traditional hydrogels lack mechanical strength. Under the action of external forces, the cross-linked structure is easily permanently damaged. In addition, their internal structure is simple and lacks special functionality. These defects have greatly limited their application.

[0003] Studies have shown that hydrophobic interaction is crucial in living systems. It can maintain the stability of cell membranes, promote the folding of protein chains to maintain the stability of their molecular structures, and enhance the toughness of cartilage connective tissue. Hydrophobic interaction is a typical non-covalent physical effect. Introducing it into the hydrogel system, the hydrophobic association microregions formed by hydrophobic interactions serve as dynamic cross-linking points, giving the hydrogel good self-healing properties and improving the mechanical strength of the hydrogel. Summary of the invention

[0004] In view of the defects in the prior art, the purpose of the present invention is to provide a super-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and its preparation method and application. The hydrogel achieves high rebound performance and high sensitivity through hydrophobic association, hydrogen bonding and metal coordination, and has potential application value in the fields of health monitoring, human-computer interaction and wearable devices, and can effectively solve the problems of low rebound efficiency, poor mechanical properties and low sensitivity of existing conductive hydrogel materials.

[0005] The first aspect of the embodiment of the present application provides a super-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and a preparation method and application thereof, comprising the following steps:

[0006] 1) Add hexadecyltrimethylammonium bromide and lithium chloride into water, stir them magnetically to form a uniform suspension, add hexadecyl methacrylate into the solution, and continue stirring until the hexadecyl methacrylate is completely dissolved to obtain a mixed solution A;

[0007] 2) Add acrylamide monomer, phytic acid and initiator to the mixed solution A, stir evenly until all are dissolved, and obtain a mixed solution B.

[0008] 3) Pour the mixed solution B into a mold and perform polymerization reaction to obtain a highly resilient and highly sensitive hydrophobic associative conductive hydrogel.

[0009] Furthermore, step 2) further includes: subjecting the mixed solution B to ultrasonic treatment to remove bubbles therein.

[0010] Furthermore, the ultrasound time is 3-5min;

[0011] The ultrasonic time is preferably 3 minutes, which ensures that bubbles can be removed while also ensuring that the hydrogel does not gel in the container due to the thermal effect generated by the ultrasonic wave.

[0012] Furthermore, in order to prevent the solution from gelling due to overheating during ultrasound, ice water bath ultrasound can be used.

[0013] Furthermore, in step 3), the polymerization reaction temperature is 40-80° C., and the polymerization reaction time is 2-4 h.

[0014] Furthermore, in step 3), the polymerization reaction temperature is 60° C. and the polymerization reaction time is 3 h.

[0015] The polymerization reaction temperature is preferably 60° C., and the polymerization reaction time is preferably 2 h to ensure complete gelation.

[0016] Furthermore, in step 1), the mass ratio of hexadecyltrimethylammonium bromide: lithium chloride: water is (0.5-1.5): (1-3): (10-50), the magnetic stirring time is 20-40 minutes, and the stirring time is continued for 5-15 minutes; or

[0017] The magnetic stirring time was 30 min, and the stirring time was continued for 10 min.

[0018] The introduction of hexadecyl methacrylate can serve as the physical cross-linking point of the hydrogel, and the hydrophobic groups can be physically cross-linked with the acrylamide chains during the polymerization of acrylamide, so that it has a uniform network structure. The addition of lithium chloride can not only promote the dissolution of hexadecyl methacrylate in the surfactant to form more hydrophobic associated micelles, but also provide freely movable ions, thereby achieving its good conductive properties.

[0019] Furthermore, in steps 1) and 2), the mass ratio of acrylamide:phytic acid is (0-2):(0-0.8), the mass ratio of initiator:water is (0.2-0.6):(50-150), and the stirring time is 20-40s.

[0020] The addition of inorganic salts can give the hydrogel excellent conductivity and antifreeze properties.

[0021] Furthermore, in step 2), the inorganic salt is selected from sodium perchloride or lithium chloride; and the initiator is selected from at least one of ammonium persulfate, potassium persulfate and sodium persulfate.

[0022] The second aspect of the present invention also provides a phytic acid-based ultra-stretchable, compression-resistant, dual-physical cross-linked conductive hydrogel, which is prepared by the above-mentioned method. The phytic acid-based ultra-stretchable, compression-resistant, dual-physical cross-linked conductive hydrogel has a strength of 378.25 kPa, an elongation at break of 859.5%, and a strain response sensitivity value GF of 1.15.

[0023] The third aspect of the present invention also provides an application of the above-mentioned ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid in health monitoring, human-computer interaction and wearable devices.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention introduces hexadecyl methacrylate as a hydrophobic unit into the gel system, forms a dynamic hydrophobic association micro-domain under the action of hexadecyltrimethylammonium bromide, and combines with the physical cross-linking network formed by the acrylamide polymer chain. The synergistic enhancement of the two makes the gel have excellent mechanical properties and high resilience (strength of 378.25 kPa, elongation at break of 859.5%).

[0026] (2) The acrylamide molecular chain in the present invention contains a large number of amino groups, which can form abundant hydrogen bonding interactions. The addition of phytic acid can promote the dissolution of the acrylamide polymer chain to form more hydrogen bonds. Phytic acid itself also provides more hydrogen bonding active sites, while giving the hydrogel excellent transparency. The tightly cross-linked network structure in the system enables the hydrogel to have rapid self-healing properties.

[0027] (3) The presence of freely movable ions in the hydrogel system of the present invention makes the hydrogel highly sensitive and can monitor the state changes of different parts of the human body (fingers, wrists, elbows and leg bending). The flexible touch screen made of hydrogel can monitor different writing signals and distinguish the action that generates the signal by analyzing the relative resistance change curve, thus having good sensing performance.

[0028] (4) The addition of lithium chloride in the present invention gives the gel excellent conductivity; at the same time, the preparation process provided by the present application is simple, has a short cycle, good controllability and is easy to achieve large-scale application; the prepared conductive hydrogel has efficient self-healing properties, high sensitivity and good mechanical properties, and has broad application prospects in the fields of health monitoring, human-computer interaction and wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. In addition, it should be understood that after reading the contents taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0030] Figure 1 It is a mechanical property test diagram of the ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid of the present invention, wherein Figure a is a tensile stress-strain curve corresponding to different hexadecyl methacrylate contents, and Figure b is a tensile stress-strain curve corresponding to different phytic acid contents;

[0031] Figure 2 This is a scanning electron microscope image of the phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel in Example 3 of the present invention.

[0032] Figure 3 This is a strain response sensitivity diagram of the ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid in Example 3 of the present application;

[0033] Figure 4 These are the sensing performance test diagrams of the ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid as a flexible touch screen under different strains in Example 3 of the present application, and Figures ad are the relative resistance change diagrams corresponding to writing the letters A, B, C, and D on the hydrogel sensor, respectively.

[0034] Figure 5 This is a compression performance test chart of the ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid in Example 3 of the present application. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] A phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel and a preparation method thereof, the steps are as follows:

[0038] 1) Add 0.8 g of hexadecyltrimethylammonium bromide and 0.4 g of lithium chloride into 5 ml of deionized water, heat and stir in a water bath for 30 min to form a uniform solution, add 25 mg of hexadecyl methacrylate into the solution, continue stirring for 5 min until the solution is uniformly dispersed, and obtain a mixed solution A; wherein the addition of lithium chloride can promote the dissolution of hexadecyl methacrylate micelles and form a stronger hydrophobic association;

[0039] 2) Add 2g acrylamide monomer, 0.1g phytic acid and 20mg potassium persulfate initiator to mixed solution A, stir for 30s to dissolve them completely, and remove bubbles in the solution by ultrasonication for 3min to obtain mixed solution B;

[0040] 3) Pour the mixed solution B into a mold, put it into an oven at 60° C. for polymerization reaction for 2 hours, and then take it out to obtain an ultra-stretchable and compression-resistant hydrophobic associative conductive hydrogel.

[0041] Example 2

[0042] A phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel and a preparation method thereof, the steps are as follows:

[0043] 1) Add 0.8 g of hexadecyltrimethylammonium bromide and 0.4 g of lithium chloride to 5 ml of deionized water, heat in a water bath for 30 min to form a uniform solution, add 50 mg of hexadecyl methacrylate to the solution, and continue stirring for 5 min until it is uniformly dispersed to obtain a mixed solution A; wherein the addition of lithium chloride can promote the dissolution of hexadecyl methacrylate micelles and form a stronger hydrophobic association.

[0044] 2) Add 2g acrylamide monomer, 0.2g phytic acid and 20mg potassium persulfate initiator to the mixed solution A, stir for 30s to dissolve them completely, and remove bubbles in the solution by ultrasonication for 5min to obtain a mixed solution B;

[0045] 3) Pour the mixed solution B into a mold, put it into an oven at 50° C. for polymerization reaction for 2 hours, and then take it out to obtain an ultra-stretchable and compression-resistant hydrophobic associative conductive hydrogel.

[0046] Example 3

[0047] A phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel and a preparation method thereof, the steps are as follows:

[0048] 1) Add 0.8 g of hexadecyltrimethylammonium bromide and 0.4 g of lithium chloride into 5 ml of deionized water, heat in a water bath for 30 min to form a uniform solution, add 75 mg of hexadecyl methacrylate into the solution, continue stirring for 5 min until the solution is uniformly dispersed, and obtain a mixed solution A; wherein the addition of lithium chloride can promote the dissolution of hexadecyl methacrylate micelles and form a stronger hydrophobic association;

[0049] S2, adding 2g acrylamide monomer, 0.1g phytic acid, and 20mg potassium persulfate initiator to the mixed solution A, stirring for 30s to completely dissolve them, and removing bubbles in the solution by ultrasonication for 5min to obtain a mixed solution B;

[0050] 3) Pour the mixed solution B into a mold, put it into an oven at 60° C. for polymerization reaction for 3 hours, and then take it out to obtain an ultra-stretchable and compression-resistant hydrophobic associative conductive hydrogel.

[0051] Example 4

[0052] A phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel and a preparation method thereof, the steps are as follows:

[0053] 1) Add 0.8 g of hexadecyltrimethylammonium bromide and 0.4 g of sodium chloride to 5 ml of deionized water, heat in a water bath for 30 min to form a uniform solution, add 100 mg of hexadecyl methacrylate to the solution, continue stirring for 5 min until the solution is uniformly dispersed, and obtain a mixed solution A; wherein the addition of sodium chloride can promote the dissolution of hexadecyl methacrylate micelles and form a stronger hydrophobic association;

[0054] 2) Add 2g acrylamide monomer, 0.4g phytic acid and 10mg potassium persulfate initiator to mixed solution A, stir for 30s to dissolve them completely, and remove bubbles in the solution by ultrasonication for 5min to obtain mixed solution B;

[0055] 3) Pour the mixed solution B into a mold, put it into an oven at 60° C. for polymerization reaction for 4 hours, and then take it out to obtain an ultra-stretchable and compression-resistant hydrophobic associative conductive hydrogel.

[0056] Example 5

[0057] A phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel and a preparation method thereof, the steps are as follows:

[0058] 1) Add 0.8 g of hexadecyltrimethylammonium bromide and 0.4 g of lithium chloride into 5 ml of deionized water, heat in a water bath for 30 min to form a uniform solution, add 125 mg of hexadecyl methacrylate into the solution, continue stirring for 5 min until the solution is uniformly dispersed, and obtain a mixed solution A; wherein the addition of lithium chloride can promote the dissolution of hexadecyl methacrylate micelles and form a stronger hydrophobic association;

[0059] 2) Add 2g acrylamide monomer, 0.8g phytic acid and 40mg ammonium persulfate initiator to the mixed solution A, stir for 30s to dissolve them completely, and remove bubbles in the solution by ultrasonication for 5min to obtain a mixed solution B;

[0060] 3) Pour the mixed solution B into a mold, put it into an oven at 80° C. for polymerization reaction for 3 hours, and then take it out to obtain an ultra-stretchable and compression-resistant hydrophobic associative conductive hydrogel.

[0061] Example 6

[0062] A phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel and a preparation method thereof, the steps are as follows:

[0063] 1) Add 0.8 g of hexadecyltrimethylammonium bromide and 0.4 g of lithium chloride into 5 ml of deionized water, heat in a water bath for 30 min to form a uniform solution, add 75 mg of hexadecyl methacrylate into the solution, continue stirring for 5 min until the solution is uniformly dispersed, and obtain a mixed solution A; wherein the addition of lithium chloride can promote the dissolution of hexadecyl methacrylate micelles and form a stronger hydrophobic association;

[0064] 2) Add 2g acrylamide monomer and 20mg potassium persulfate initiator to mixed solution A, stir for 30s to dissolve them completely, and remove bubbles in the solution by ultrasonication for 5min to obtain mixed solution B;

[0065] 3) Pour the mixed solution B into a mold, put it into an oven at 80° C. for polymerization reaction for 3 hours, and then take it out to obtain an ultra-stretchable and compression-resistant hydrophobic associative conductive hydrogel.

[0066] The properties and morphology of the hydrogels prepared in Examples 1-6 are analyzed as follows.

[0067] The prepared phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel was cut into standard strips with a width of 5 mm and a length of 14 mm, and mechanical properties were tested using a universal material testing machine (Shenzhen Sansi Zongheng Technology Co., Ltd.) at a test speed of 50 mm / min. Figure 1This is a mechanical property test diagram of the ultra-stretchable, compression-resistant, dual-physical cross-linked conductive hydrogel based on phytic acid of the present invention, wherein Figure a is the tensile stress-strain curve corresponding to different HMA contents, and Figure b is the tensile stress-strain curve corresponding to different phytic acid contents. It can be seen from the figure that with the increase of HMA content and phytic acid content, the tensile strength of the hydrogel first increases and then decreases, and the elongation at break first increases and then decreases. When the addition amount of HMA is 75 mg and the addition amount of phytic acid is 0.1 g, it has the most excellent mechanical properties, wherein the mechanical strength is 378.25 kPa and the elongation at break is 859.5%.

[0068] Morphology analysis: The morphology of the conductive hydrogel prepared in Example 3 was observed by scanning electron microscopy. Figure 2 As shown, the hydrogel exhibited a well-developed 3D porous structure.

[0069] The ultra-stretchable, compression-resistant, dual-physical cross-linked conductive hydrogel based on phytic acid in Example 3 was connected to a universal testing machine to control different deformations (100%-500%) and a fixed stretching rate of 50 mm / min. The relative resistance change curve caused by different deformations was recorded in real time by an electrochemical workstation. The test results are shown in Figure 3 The strain response sensitivity value of the hydrogel sensor is greater than 1, indicating that it has very excellent conductive properties and sensitivity.

[0070] The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid in Example 3 was connected to an electrochemical workstation, and different English letters were written on the gel, and the relative resistance change curve caused by different positions and different pressures was recorded in real time by the electrochemical workstation. The test results are shown in Figure 4 The hydrogel sensor shows different electrochemical signals for different letters. When the pressure is removed, the sensor can immediately restore its original resistance value, and its relative resistance change maintains good repeatability and stability.

[0071] The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid in Example 3 was designed into a cylindrical shape with a diameter of 15 mm and a height of 10 mm, as shown in FIG. Figure 5 As shown, the gel is placed on a universal testing machine and the compression deformation is controlled to 80%. After 10 cycles, the hydrogel can still return to its original shape. The prepared hydrogel sensor has good compression resistance.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. Phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel and its preparation method, characterized in that: The following steps are involved: 1) adding hexadecyltrimethylammonium bromide and lithium chloride into water, stirring them by magnetic force to form a uniform suspension, adding hexadecyl methacrylate into the above solution, and continuing to stir until the hexadecyl methacrylate is completely dissolved, to obtain a mixed solution A; 2) adding acrylamide monomer, phytic acid and initiator to the mixed solution A, stirring evenly until all of them are dissolved, to obtain a mixed solution B; 3) pouring the mixed solution B into a mold to carry out micelle polymerization reaction to obtain an ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel.

2. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and the preparation method thereof according to claim 1, characterized in that: Step 2) further includes: subjecting the mixed solution B to ultrasonic treatment to remove bubbles therein.

3. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and the preparation method thereof according to claim 2, characterized in that: The ultrasonic time is 3-5min.

4. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and the preparation method thereof according to claim 1, characterized in that: In step 3), the polymerization reaction temperature is 40-80° C., and the polymerization reaction time is 2-4 hours.

5. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and the preparation method thereof according to claim 4, characterized in that: In step 3), the polymerization reaction temperature is 60° C. and the polymerization reaction time is 2 h.

6. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and the preparation method thereof according to claim 1, characterized in that: In step 1), the mass ratio of hexadecyltrimethylammonium bromide: lithium chloride: water is (0.5-1.5): (1-3): (10-50), the magnetic stirring time is 20-40 minutes, and the stirring time is continued for 5-15 minutes.

7. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and the preparation method thereof according to claim 1, characterized in that: In steps 1) and 2), the mass ratio of acrylamide:phytic acid is (0-2):(0-0.8), the mass ratio of initiator:water is (0.2-0.6):(50-150), and the stirring time is 20-40s.

8. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid and the preparation method thereof according to claim 1, characterized in that: In step 1), the inorganic salt is at least one of sodium chloride, lithium chloride, magnesium chloride and copper chloride; in step 2), the initiator is at least one of ammonium persulfate, potassium persulfate and azobisisobutyronitrile.

9. The ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel based on phytic acid according to claim 1, characterized in that: The high-resilience, high-sensitivity hydrophobic association conductive hydrogel prepared by the method described in any one of claims 1 to 8 has a strength of 350-500 kPa, an elongation at break of 800-1200%, and a strain response sensitivity value GF of 0.8-1.

5.

10. Application of the phytic acid-based ultra-stretchable, compression-resistant, double-physical cross-linked conductive hydrogel sensor according to claim 9 in health monitoring, deformation sensors and wearable devices.

Citation Information

Patent Citations

  • Self-repairing conductive double network structure hydrogel and preparation method thereof

    CN108440772A

  • Dual-network conductive hydrogel, preparation method thereof and flexible wearable electronic equipment

    CN114479125A

  • Self-healing gel based on dynamic non-covalent bond interaction as well as preparation method and application of self-healing gel

    CN114957538A

  • Preparation method of conductive hydrogel with mechanical property and anti-swelling property

    CN117050338A

  • Conductive self-healing network

    US20170292008A1